Ineficacia de la reparación económica dentro de la acción de protección constitucional - Espinosa Guajala, Wilson Oswaldo (2023)
This paper analsed the connection between the action of protection and economic reparation from a critical perspective, within the framework of the constitutional State of rights. The descriptive methodology was based on a mixed approach: qualitative, through the theoretical foundation of the object of study and quantitative, through the statistical treatment of the information. Similarly, the following methods were used: dogmatic, inductive-deductive, synthetic analytical and historical-logical, as well as the techniques of bibliographic review, file, and a survey to the constitutional judges from the Ambato canton. It is concluded that there is ineffectiveness in economic reparation in the country's constitutional protection, so it is imperative that the institutions and people who make up the constitutional justice directly and indirectly, observe, comply and abide by the constitutional rule and the processes derived from it, in order to ensure a true protection of all fundamental rights.